2003
DOI: 10.1016/s0893-6080(03)00093-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolving efficient learning algorithms for binary mappings

Abstract: Abstract-Gradient descent training of sigmoidal feed-forward neural networks on binary mappings often gets stuck with some outputs totally wrong. This is because a sum-squared-error cost function leads to weight updates that depend on the derivative of the output sigmoid which goes to zero as the output approaches maximal error. Although it is easy to understand the cause, the best remedy is not so obvious. Common solutions involve modifying the training data, deviating from true gradient descent, or changing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 8 publications
1
50
0
Order By: Relevance
“…The neural network architecture and training data were as described above, and a few simple tests determined that 20 hidden units were adequate to learn the training data, and that 1200 data samples per simulated year provided adequate performance estimates for both testing and training purposes. Similar studies [12,13,15] have found empirically that the evolved parameters range over many orders of magnitude, so it was computationally efficient to apply the crossovers and mutations to the logarithms of the parameters, rather than the parameters themselves. The additive mutations were based on a mixture of two sufficiently wide…”
Section: Baseline Simulation Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…The neural network architecture and training data were as described above, and a few simple tests determined that 20 hidden units were adequate to learn the training data, and that 1200 data samples per simulated year provided adequate performance estimates for both testing and training purposes. Similar studies [12,13,15] have found empirically that the evolved parameters range over many orders of magnitude, so it was computationally efficient to apply the crossovers and mutations to the logarithms of the parameters, rather than the parameters themselves. The additive mutations were based on a mixture of two sufficiently wide…”
Section: Baseline Simulation Resultsmentioning
confidence: 79%
“…Earlier evolutionary studies [13,15,16] found that the evolutionary efficiency depends rather strongly on the initial conditions, i.e. on the distribution of innate parameters across the initial population.…”
Section: Baseline Simulation Resultsmentioning
confidence: 97%
See 3 more Smart Citations